O impacto econômico regional do Parque Tecnológico Itaipu (PTI) - Lucizani, Jonhey Nazario (2012)
This work has prospected and analyzed the economic impacts of the Itaipu Technological Park (PTI), hereinafter referred to as impacts on income generation, production and jobs in the Parana, as the economy of the PTI. For this, we used the input-output matrix, using the search field in the PTI organizations to collect accounting information. This information led to the final demand by economic sector of the park, making it possible to design the input-output matrix. The results showed that as the value added to the economy of the PTI was R $ 27,186,350.04, with 55.5% went to employees, the final demand of the PTI was R $ 48,211,646.08, which enabled identify the income multipliers of the PTI is equal to 2.23, 1.52 employment and production equal to 2.28. The PTI was identified as a Park Structuring because accumulated regional experience and is intimately associated with the process of economic and technological development.